(untitled) (American Journal of Islam and Society, 1987)
Introduction Ghazali’s approach to usul al-fiqh, as articulated in his last and greatest work of Law, al-Mustasfa is based on the premise that, in essence, this science is knowledge of how to extract ahkam (rules) from the Shari’ah sources. (As for the science of fiqh, it concerns itself particularly with the Shari’ah rules themselves which have been established in order to qualify the acts of the locus of obligation, man.) Accordingly, Ghazali views it as imperative that any discourse on usul focus on three essentail elements: the ahkam; the adilla (sources); and the means by which rules are extracted from these sources, which ultimately includes examination of the qualifications of the extractor, namely, the mujtahid. This paper lays out Ghazali’s treatment in al-Mustasfa of the first of these elements, the ahkam. Hukm (The Shari’ah Address) Linguistically, hukm is the verbal noun of hakama, which signifies “withholding, restraint, prevention; and judgment, jurisdiction, rule, dominion, authority, or governinglq The technical meaning, however, varies according to its usages in the terminologies of philosophy, Arabic grammar, usul, and fiqh. Ghazali defines hukm as the Shan‘irh address ( khitab al-Shar’) in relation to the acts of the loci of obligation, the address being Allah’s revelation to His Messenger. It is divided into two categories: revelation for recitation (wahi matluww), that is, the Qur”an; and revelation not for recitation (wahi ghayr lww matu), namely, the Sunnah.